Study Criteria Applied to Real Life—A Multicenter Analysis of Stroke Patients Undergoing Endovascular Treatment in Clinical Practice - Hannes Leischner (Wiley, 2021)
Background Randomized controlled clinical trials (RCT) have demonstrated the efficacy of endovascular treatment in anterior circulation large vessel occlusions. However, outcome of patients treated in daily practice differs from the results of the clinical trials. We hypothesize that this is attributable to the study criteria and that application of the criteria on patients undergoing endovascular therapy in daily routine would improve their outcome. Methods and Results Data from a multicenter prospective registry of GSR‐ET (German Stroke Registry – Endovascular Treatment) was used. Inclusion criteria and selectivity of SWIFT‐PRIME (Solitaire with the Intention for Thrombectomy as Primary Endovascular Treatment trial), MR CLEAN (Multicenter Randomized Clinical Trial of Endovascular Treatment for Acute Ischemic Stroke in the Netherlands trial), ESCAPE (Endovascular Treatment for Small Core and Anterior Circulation Proximal Occlusion with Emphasis on Minimizing CT to Recanalization Times trial), DAWN (DWI or CTP Assessment with Clinical Mismatch in the Triage of Wake‐Up and Late Presenting Strokes Undergoing Neurointervention with Trevo trial) and DEFUSE‐3 (Endovascular Therapy Following Imaging Evaluation for Ischemic Stroke trial) trials were analyzed. Baseline characteristics, procedural and outcome data of patients from GSR‐ET before and after selection were compared with the results of the RCTs. Furthermore, outcome of patients who underwent endovascular treatment despite not fulfilling the RCT criteria was analyzed. A total of 2611 patients were included (median age, 75 years; 49.6% women; median National Institute of Health Stroke Scale, 16). A minority of patients met all inclusion criteria, ranging from 3% (DEFUSE‐3 criteria) to 35% (MR CLEAN criteria). Of the patients fulfilling the MR CLEAN criteria, 41% of patients had a good clinical outcome, compared with 34% of patients that did not fulfill MR CLEAN criteria. Conclusions The RCTs represent a selected population with higher rates of good clinical outcome compared with daily practice. The good outcomes of RCTs can be reproduced in clinical routine in patients who fulfill the RCT inclusion criteria. Furthermore, patients who did not meet the criteria of the RCT still had substantial rates of good clinical outcome.